Proceedings 2018 Network and Distributed System Security Symposium 2018
DOI: 10.14722/ndss.2018.23309
|View full text |Cite
|
Sign up to set email alerts
|

Riding out DOMsday: Towards Detecting and Preventing DOM Cross-Site Scripting

Abstract: Cross-site scripting (XSS) vulnerabilities are the most frequently reported web application vulnerability. As complex JavaScript applications become more widespread, DOM (Document Object Model) XSS vulnerabilities-a type of XSS vulnerability where the vulnerability is located in client-side JavaScript, rather than server-side code-are becoming more common. As the first contribution of this work, we empirically assess the impact of DOM XSS on the web using a browser with taint tracking embedded in the JavaScrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 10 publications
1
56
0
Order By: Relevance
“…First, state-of-the-art automated techniques for detecting XSS vulnerabilities in the web typically work with client-side XSS [33,35,49,53], whereas the XSS attacks against cloud-application add-ons may also exist on the server side. For example, the vulnerabilities of MS Office Online add-ons are always on the client side because the attacker's malicious input is propagated to the add-on via local messaging (i.e.…”
Section: Analysis Methodologymentioning
confidence: 99%
“…First, state-of-the-art automated techniques for detecting XSS vulnerabilities in the web typically work with client-side XSS [33,35,49,53], whereas the XSS attacks against cloud-application add-ons may also exist on the server side. For example, the vulnerabilities of MS Office Online add-ons are always on the client side because the attacker's malicious input is propagated to the add-on via local messaging (i.e.…”
Section: Analysis Methodologymentioning
confidence: 99%
“…Our attack also utilizes cross-domain file inclusion to launch the SW-XSS attack, thus we share the same sentiment regarding this issue. In recent years, a variant of XSS called DOM-XSS is emerging [17,18,23]. DOM-XSS can be similar to our attack in a sense that it allows attackers to execute remote code on the client-side.…”
Section: Related Workmentioning
confidence: 99%
“…We only investigate CSP in isolation. In addition to that, research has shown that a non-negligible fraction of sites suffers from markup injection vulnerabilities [13,15,30].…”
Section: Limitations and Potential Modificationsmentioning
confidence: 99%